2019
DOI: 10.1017/s1047951119000738
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative serum albumin and its influence on clinical outcomes in neonates and infants undergoing cardiac surgery with cardiopulmonary bypass: a multi-centre retrospective study

Abstract: Hypoalbuminemia is associated with morbidity and mortality in critically ill children. In this multi-centre retrospective study, we aimed to determine normative values of serum albumin in neonates and infants with congenital heart disease, evaluate perioperative changes in albumin levels, and determine if low serum albumin influences post-operative outcomes. Consecutive eligible neonates and infants who underwent cardiac surgery with cardiopulmonary bypass at one of three medical centres, January 2012–August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
12
2
2
Order By: Relevance
“…In children receiving cardiac surgery, hypoalbuminemia is associated with an increased length of hospital stay and mortality (21,22). However, in this study, the serum albumin 10.3389/fnut.2022.931599…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In children receiving cardiac surgery, hypoalbuminemia is associated with an increased length of hospital stay and mortality (21,22). However, in this study, the serum albumin 10.3389/fnut.2022.931599…”
Section: Discussioncontrasting
confidence: 51%
“…In children receiving cardiac surgery, hypoalbuminemia is associated with an increased length of hospital stay and mortality ( 21 , 22 ). However, in this study, the serum albumin levels did not appear to be not associated with mortality in children receiving cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Serum albumin is considered as a marker of disease severity in critically ill adult patients, with low serum albumin concentrations being reported in 30%-50% of cases 12,13 . Some studies have investigated the incidence and the prognostic value of hypoalbuminemia in critically ill children, reporting a higher incidence (60% approximately) in cases requiring PICU admission 11,[16][17][18][19][20][21][22] . In our study, hypoalbuminemia, defined as serum levels less than 3.5 g/dl, was observed in approximately 15% of cases of AB at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hypoalbuminemia has been previously shown as a significant marker of mortality and increased stay in children admitted to pediatric intensive care unit 11,[16][17][18][19][20][21][22] , but to our knowledge this is the second study that have investigated the role of hypoalbuminemia as biomarker for severity in children with AB. Mansbach et al studied 1016 infants with AB and found that those cases of AB presenting with hypoalbuminemia had a four-fold risk to develop apnea during hospitalization 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gibbs et al, using a multiple regression model, demonstrated that postoperative day 1 serum albumin level was an independent predictor of postoperative complications [ 11 ]. Although few studies [ 1 , 12 ] have examined postoperative serum albumin levels in children after cardiac surgeries, there is a paucity of data on peri-operative serum albumin levels in children undergoing emergency abdominal surgeries. Therefore, in this study, we aim to investigate the correlation between the degree of peri-operative fall in serum albumin levels and the outcomes in children undergoing emergent abdominal surgeries.…”
Section: Introductionmentioning
confidence: 99%